An Examination of the Effectiveness of Child Endangerment Laws in Preventing Child Fatalities in Alcohol-Involved Motor Vehicle Crashes - Kelley-Baker, Tara (J Stud Alcohol Drugs, 2016)
OBJECTIVE: The aim of this study was to assess the impact of U.S. child-endangerment laws on the prevalence of child passengers fatally injured in motor vehicle crashes in which the adult driver was drinking. METHOD: We used data from the 2002–2012 Fatality Analysis Reporting System. We conducted both bivariate and multivariate analyses using Heckman selection models. RESULTS: After adjusting for several cofactors, including driver demographics and blood alcohol concentration, child seat positioning, and seat belt laws, we found that passing a DUI child-endangerment law may have no impact at all on the likelihood of finding impaired drivers among those driving with children. CONCLUSIONS: There are a number of reasons why DUI child-endangerment laws have not been effective in saving the lives of young passengers who are driven by adult drinking drivers. These reasons include lack of publicity and education, as well as issues related to enforcement. Potential solutions are suggested that include examining sanctions and strengthening of DUI child endangerment laws.